Penerapan Metode Tutor Sebaya dalam Meningkatkan Keterampilan Sosial Siswa Kelas IV SD - Alliyah Putri Supriyatna; Nurdinah Hanifah; Isrok'atun (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
In learning, methods are widely used to help students understand the material more easily. One of them is the peer tutoring method. The peer tutoring method is where students are appointed or given responsibility for helping other friends who are experiencing difficulties. This is supported by a closer friendship than the close relationship between teacher and student. Likewise, peer tutoring can improve students' social skills to be confident, active and responsible in learning and communicating well. This research aims to find out how the peer tutoring method is implemented, the obstacles to the peer tutoring method and to find out the use of the peer tutoring method to improve students' social skills. The fact was found that this research was conducted on social studies learning, there were five students in the fourth grade at SDN Pakualam 02 South Tangerang, who tended to be indifferent to the activities carried out because in the learning process the teacher still used conventional methods such as lectures. Through the peer tutoring method, you can create interesting teaching so that students don't get bored quickly with social studies learning and can improve their social skills to interact with their friends. Therefore, in this research the peer tutoring method is used as material to be researched and studied. The method used to conduct this research is a qualitative descriptive method which uses data in the form of information based on findings in the field through observation, interviews and filling out questionnaires. Based on the findings of this research, the application of the peer tutoring method showed positive changes in five students in the formation of groups during social studies learning which could effectively increase students' desire to be skilled at each other and solve problems understanding the learning material together.